2023
DOI: 10.3390/nano13071285
|View full text |Cite
|
Sign up to set email alerts
|

Thymol-Nanoparticles as Effective Biocides against the Quarantine Pathogen Xylella fastidiosa

Abstract: Quarantine pathogens require the investigation of new tools for effective plant protection. In particular, research on sustainable agrochemicals is the actual challenge. Plant extracts, essential oils, and gels are natural sources of efficient biocides, such as aromatic secondary metabolites. Thymol is the major phenolic constituent of thyme and oregano essential oils, and it can inhibit many pathogenic microbes. Thymol nanoparticles were obtained through adsorption on CaCO3 nanocrystals, exploiting their carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…These include biocides such as aromatic secondary metabolites naturally found in plant extracts, essential oils and gels. Baldassarre et al [ 150 ], using both a fluorometric assay and an in vitro inhibition assay, published the first investigation of the impact of thymol on Xfp. This study demonstrated the powerful antibacterial properties due to synergistic interaction between thymol and CaCO 3 nanocarriers, suggesting the possible use of these agrochemical formulations as efficient biocides to control Xfp infection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These include biocides such as aromatic secondary metabolites naturally found in plant extracts, essential oils and gels. Baldassarre et al [ 150 ], using both a fluorometric assay and an in vitro inhibition assay, published the first investigation of the impact of thymol on Xfp. This study demonstrated the powerful antibacterial properties due to synergistic interaction between thymol and CaCO 3 nanocarriers, suggesting the possible use of these agrochemical formulations as efficient biocides to control Xfp infection.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various on field treatments, which include the use of mineral solutions [ 153 ], as well as vegetable oils and extracts from various botanical species [ 145 ], zinc and copper administration as the citrate biocomplex prevails [ 117 , 135 , 136 , 139 , 143 , 144 , 147 , 149 , 151 ]. In addition, 42.11% of scientific works (eight documents) refer to in vitro testing with the aim of selecting potential antimicrobial compounds to be used in infected plants [ 137 , 142 , 148 , 150 , 154 ] or identifying antagonistic organisms potentially deployable as biocontrol agents against Xf [ 140 , 141 ]. Both fields of intervention (on field and in vitro) are jointly reported in three documents (15.79%), where the research included field testing after in vitro effectiveness testing of the same compounds [ 135 , 143 , 152 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, thymol as itself, which was one the main constituents of the Th-EO used in this work, was positively used to inhibit R. solanacearum and several Xanthomonas species, the causal agents of bacterial wilt and leaf spot in many crops [36]. A great growth inhibition activity of this compound has been demonstrated in X. fastidiosa cells and has been greatly enhanced by nanoencapsulation and smart delivery [39]. Even cymene was positively assayed for its antimicrobial properties on several microorganisms, including nematodes, fungi, and food-borne bacteria, in both its natural forms (para and ortho) [67,68].…”
Section: Biological Properties Of Th-eo and Cncs@th-eo Nementioning
confidence: 94%
“…Thymol, the primary phenolic component of thyme (Thymus vulgaris) essential oil, displays rapid activity against gram-negative and gram-positive bacteria compared with other plant metabolites [36,37]. Recently, we found a great inhibition activity towards Xylella fastidiosa for thymol, which was improved through the carrier action of CaCO 3 nanocrystals [38,39].…”
Section: Introductionmentioning
confidence: 99%